The kinase insert domain-containing receptor is an angiogenesis-associated antigen recognized by human cytotoxic T lymphocytes - Sun, Yuansheng; Song, Mingxia; Schadendorf, Dirk (Blood, 2005)
Antigen-specific cancer immunotherapy directed toward tumor-nourishing angiogenic blood vessels holds the promise of high efficacy, low toxicity, and ease of application. To evaluate whether the human angiogenic kinase insert domain-containing receptor (KDR) can serve as a target for cellular immunotherapy, 19 peptide sequences with HLA-A*0201 motifs were selected by computer-based algorithms. Five peptides (KDR82-90, KDR288-297, KDR766-774, KDR1093-1101, KDR1035-1044) stimulated specific cytotoxic T lymphocytes (CTLs) from peripheral-blood mononuclear cells (PBMCs) of 3 HLA-A*0201 donors. The decapeptide KDR288-297 was efficient in sensitizing target cells for recognition by a CTL clone at a concentration of 10 nM. More important, KDR288-297 - specific CTLs lysed target cells transfected with HLA-A2/KDR cDNAs and a range of HLA-matched KDR+ angiogenic endothelial cells (aECs) and also recognized CD34+ endothelial progenitor cells. The specificity of CTLs was further confirmed by tetramer assay and cold-target inhibition assay. In addition, ex vivo exposure of aECs to the inflammatory cytokines enhanced CTL reactivity, which is in keeping with up-regulated KDR and HLA class 1 expression. In Matrigel assays, recognition of aECs by specific CTLs triggered an antivascular effect. These findings provide the first proof of the antigenic property of KDR protein and may be useful for devising new immunotherapeutic approaches to human cancers.
Prepublished online as Blood First Edition Paper, October 18, 2005
Gesehen am 22.01.2021